Analysis of Cost and Returns of the Pineapple Cultivation in Manipur - Singh, Ningombam Anandkumar; Singh, Ram; Feroze, S. M.; Singh, Rajkumar Josmee (Indian Journal of Hill Farming, 2016)
Pineapple is an importance fruit crop in the state of Manipur. Keeping this in view, a study has been conducted on analysis of cost and return of pineapple cultivation in two seasons i.e., summer and winter for the years 2011-12 and 2013-2014 in Manipur. The overall per ha cost of cultivation (C2) of pineapple were estimated to be `54506.65, `24410.46 and `35671.51 in first, second and third year during summer and `9097.83, `15704.08 and `21885.97 during winter season. The Cost A1 was `40848.60, `13074.37 and `19622.93 in first, second and third year during summer and `2616.91, `7080.67 and `10198.75 during winter season. The Cost A1, A2 and Cost B1 were same because none of the respondents have leased in any land and interest on fixed capital in both the season. The Cost B2 was `46848.60, `19074.37 and `25622.93 in first, second and third year during summer and `8616.91, `13080.67 and `16198.75 during winter season and Cost C1 was `48506.65, `18410.46 and `29671.51 in first, second and third year during summer and `3097.83, `9704.08 and `15885. during winter season. The gross return was `53436.60 in second year and `92813.72 in third year during summer and `21601.63 and `37470.19 during winter season. The net farm return was highest in second year in both seasons i.e., `57142.20 and `21271.44 compared to the net return in second year i.e., `29026.13 and `8520.96 during summer and winter season. The Cost-Benefit ratio was work out to be 1.23 and 1.24 during summer and winter season.